(untitled) (Itinera, 2013)
The mimesis of regression is an artistic strategy that challenges the symbolic order. This challenge has some controversial points, since on the one hand the symbolic order proves to be extremely resistant as it manages to integrate the mimesis of regression in its structure, on the other hand the mimesis of regression itself seems to facilitate its integration by repeating the representation of the object without politicizing it. In the first section of this paper I analyse some of the most representative works based on the mimesis of regression; in the second section, I examine the controversial points in the relationship between the mimesis of regression and the symbolic order, aiming to demonstrate that the mimesis of regression loses its challenge, since it emerges to confirm the symbolic order.